Diversity of robber flies (Diptera: Asilidae) in a tropical deciduous forest of central Mexico - Bello-Morales, Frida Alejandra; Sandoval-Ruiz, César Antonio; Estrada, Alejandro (Instituto de Ecología, A.C., 2020)
Robber flies are an important group in ecosystems, because of their ecological role as predators, thus contributing to maintain a balance in insect populations. Nevertheless, little is known about their diversity and ecological interactions in Mexico. In this study, we analyzed the structure of a community of robber flies collected during three years in a tropical deciduous forest of central Mexico. In this type of vegetation, the dry and rainy seasons are contrasting and generate drastic biotic and abiotic changes that could impact on robber fly populations. Therefore, we compared the structure of the robber fly community across three seasons: cold, dry, and rainy. We collected a total of 191 individuals which included eight species and 21 morphospecies. The rainy season presented higher species richness and diversity, as well as a species composition that differed from that of the cold and dry seasons. However, abundance did not vary significantly across seasons. We also record 14 genera and ten species previously unregistered in the state of Puebla.